Scorpia - Horowitz, Anthony, 1955- (New York : Speak, 2006)
After being told that his father was an assassin for a criminal organization, fourteen-year-old Alex goes to Italy to find out more and becomes involved in a plan to kill thousands of English school children.
First published: London : Walker Books, 2004.
First American edition: Philomel Books, 2005.
5.8
5-8
5-8.
School Library Journal
Keywords: Terrorism -- Juvenile fiction; Orphans -- Juvenile fiction; Italy -- Juvenile fiction; London (England) -- Juvenile fiction; Spies -- Fiction; Terrorism -- Fiction; Orphans -- Fiction; Italy -- Fiction; London (England) -- Fiction; England -- Fiction; Adventure and adventurers -- Fiction; Spy stories; Terrorism -- Fiction; Orphans -- Fiction; Italy -- Fiction; London (England) -- Fiction; England -- Fiction; Adventure fiction; Spy stories; Adventure fiction